Promotional effect of doping SnO2 into TiO2 over a CeO2/TiO2 catalyst for selective catalytic reduction of NO by NH31. Issue 4 (24th April 2015) - Zhang, Lei; Li, Lulu; Cao, Yuan; Xiong, Yan; Wu, Shiguo; Sun, Jingfang; Tang, Changjin; Gao, Fei; Dong, Lin
<x xml:space="preserve">Abstract</x> The promotional effect of SnO2 in a Ce/TiO2 catalyst for NH3-SCR reaction.